Intravascular Large B-Cell Lymphoma Presenting as Interstitial Lung Disease - Elham Vali Khojeini; Joo Young Song (Case Reports in Pathology)
Intravascular large B-cell lymphoma (IVLBL) is a rare subtype of diffuse large B-cell lymphoma that resides in the lumen of blood vessels. Patients typically present with nonspecific findings, particularly bizarre neurologic symptoms, fever, and skin lesions. A woman presented with shortness of breath and a chest CT scan showed diffuse interstitial thickening and ground glass opacities suggestive of an interstitial lung disease. On physical exam she was noted to have splenomegaly. The patient died and at autopsy was found to have an IVLBL in her lungs as well as nearly all her organs that were sampled. Although rare, IVLBL should be included in the differential diagnosis of interstitial lung disease and this case underscores the importance of the continuation of autopsies.